Strategi Pemerintah Daerah Poso Periode 2010-2015 dalam Menghadapi Konflik Sosial - Zulkifli Hi Manna; Inu Kencana Syafiie (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this study was 1) to determine the government’s strategy in dealing with the Poso area of socialconflict and 2) to assess the constraints faced by local governments in dealing with conflict in Poso sosial.Jenis in thisresearch is a qualitative descriptive study using a case study approach took place in Poso, Central Sulawesi. Descrip-tive study (descriptive research) is a research method that is intended to describe the phenomena that exist, whichtakes place in the present or the past. Methods of data collection in this research is to use interviews and documen-tation. The informant in this research is the Local Government Poso, Poso Regional Police and Community LeadersPoso. Results from the study is that there are three strategies Poso district governments in the face of social conflicts.The first economic development policy by opening jobs, economic empowerment, providing educational facilities andhealth facilities. Both of multicultural education by building schools harmony in collaboration with religious leaders andreligious organizations. The third inter-religious dialogue by establishing the Forum for Religious Harmony which isfunded budget. While the constraints faced by the local authorities in the face of social conflict in Poso: First there is no permanent reconciliation. Both recovery funds for humanitarian tragedy of the central government has not been well targeted and Third stigma that religion causes conflict. The results of this study can be used as a reference for otherregions in anticipation of a conflict that could lead to social conflict. The conflict in the region is generally caused byeconomic factors, but wrapped in religious conflicts.